顎関節に発生したびまん型腱滑膜巨細胞腫の1例 - 吉田, 俊一; 大山, 定男; 莇生田, 整治; 小川, 千晴; 船田, 信顕; 内田, 育宏 (日本口腔外科学会雑誌, 2017)
Tenosynovial giant-cell tumors are classified into diffuse and localized types. The diffuse type develops primarily in major joints and rarely in the temporomandibular joint. We report a diffuse-type tenosynovial giant-cell tumor that developed in the temporomandibular joint, along with a discussion of the literature. A 27-year-old woman visited our hospital because of pain in the right temporomandibular joint and difficulty in mouth opening as chief complaints. Radiological examination showed a lesion in the right side of the temporomandibular joint. The histopathological diagnosis on biopsy was a tenosynovial giant-cell tumor of the diffuse type, and we performed tumor excision with the patient under general anesthesia. There has been no evidence of recurrence as of 3 years 2 months after the operation. However, continuous strict follow-up is needed in consideration of the high recurrence rates.